Analysis of human growth hormone gene 5' sequences in isolated growth hormone deficiency patients. Issue 1 (January 1994) - Wang, Y; Yu, L L; Sheng, Q; Meng, C; Sun, J; Chen, S S
Abstract : Human growth hormone (hGH) gene deletion (6.7 to 7.6 kb) is one of the causes of isolated growth hormone deficiency (IGHD), named IGHD IA. IGHD IA, however, only accounts for about 10% of the total IGHD patients. Most IGHD is caused by unknown mechanisms. Here, hGH gene 5' sequences in three IGHD patients without hGH gene deletion were analysed to see if there was any mutation hindering the expression of the hGH gene.